2002
DOI: 10.1108/jpbafm-14-02-2002-b005
|View full text |Cite
|
Sign up to set email alerts
|

Budgeting structures and citizen participation

Abstract: This paper reviews the literature concerning when and in what way citizen participation can have an impact on budgeting. The first part of the paper conceptualizes, through the literature, five budgeting models, each having both problems and solutions for citizen involvement. The second section of the paper explores intervention designs that can be constructive in dealing with the larger problems connecting budgeting and citizen participation. The paper, therefore, seeks to determine where participation in bud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 10 publications
0
24
0
Order By: Relevance
“…Previous research has identified a variety of factors relevant to participatory practices in the budget process. Four aspects have been explored: (1) who participates (Callahan, 2002;Franklin & Ebdon, 2007;Miller & Evers, 2002;Orosz, 2002;Simonsen & Robbins, 2000); (2) the context of when participation is or should be used (Ebdon & Franklin, 2006;Kathlene & Martin, 1991;King, Feltey & Susel, 1998), (3) how participation processes are conducted (Adams, 2004;Blair, 1976;Ebdon & Franklin, 2006;Ferris, 1982;Franklin & Ebdon, 2007;Hatry & Blair, 1976;Webb & Hatry, 1973;Irvin & Stansbury, 2004;Janis, 1982;1991;Morgan, 1997;Roberts, 1997;Thomas, 1995;and (4) what factors demonstrate the effectiveness of participation (Franklin, Ho, & Ebdon, 2009). This research seeks to expand this established body of literature by exploring relationships between participatory practices and governance relationships, and by focusing on perceptions of elected officials.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous research has identified a variety of factors relevant to participatory practices in the budget process. Four aspects have been explored: (1) who participates (Callahan, 2002;Franklin & Ebdon, 2007;Miller & Evers, 2002;Orosz, 2002;Simonsen & Robbins, 2000); (2) the context of when participation is or should be used (Ebdon & Franklin, 2006;Kathlene & Martin, 1991;King, Feltey & Susel, 1998), (3) how participation processes are conducted (Adams, 2004;Blair, 1976;Ebdon & Franklin, 2006;Ferris, 1982;Franklin & Ebdon, 2007;Hatry & Blair, 1976;Webb & Hatry, 1973;Irvin & Stansbury, 2004;Janis, 1982;1991;Morgan, 1997;Roberts, 1997;Thomas, 1995;and (4) what factors demonstrate the effectiveness of participation (Franklin, Ho, & Ebdon, 2009). This research seeks to expand this established body of literature by exploring relationships between participatory practices and governance relationships, and by focusing on perceptions of elected officials.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Process-and mechanism-design characteristics posited as likely to foster meaningful participation and thereby legitimacy, responsiveness, and/or citizenship within U.S. local-government environments include: (a) making the process open and accessible to all; (b) ensuring that a representative sample of citizens participates; (c) providing for two-way communication between officials and other participants, ideally in such a way that all participants learn from one another in the process; (d) ensuring that participants incorporate a realistic budget constraint into their choices and deliberations and confront the resulting tradeoffs, and that citizen participants correctly reveal their preferences under those conditions; and (e) ensuring that participation occurs early enough in the budget cycle-typically during formulation of the budget-to be independently influential, rather than simply reactive (Ebdon & Franklin, 2004;Justice, Melitski, & Smith, 2006;Miller & Evers, 2002;Simonsen & Robbins, 2000).…”
Section: Democratic Administration and Theories-in-usementioning
confidence: 99%
“…In the context of budgeting specifically, there is the additional obstacle of non-specialists' distaste for budget and financial data. There are also particular difficulties associated with achieving adequate understanding of budget constraints and tradeoffs, the long-term implications of allocation choices, the effects of uncontrollable and/or nonnegotiable costs on budgetary discretion, and other "budget knots" (Miller & Evers, 2002). In short, it often seems that "most citizens do not possess the information and cannot afford the time to come to well-reasoned judgments about the complex issues facing government decision makers" (Simonsen & Robbins, 2000, p. 26).…”
Section: Practicalitiesmentioning
confidence: 99%
“…Initial participants are not always representative of their communities (Ebdon, 2000). In addition, those who come forward to participate may underestimate the structural complexity of budgeting (Miller & Evers, 2002). the specialized knowledge and terminology introduced by experts into the current system may be a serious barrier to meaningful citizen participation (Callahan, 2002;DeSario & Langton, 1987;Fisher, 1993).…”
mentioning
confidence: 99%
“…Both Berman (1997) and Ebdon (2002) argue that contemporary budgeting is inherently complex and difficult to understand for many people because they do not know how to obtain answers to their questions. Moreover, as Miller and Evers (2002) insist, most public officials view participation by citizens who lack basic knowledge as a road to increased conflict. thus, many public administrators and elected officials are reluctant to involve citizens in the budget process (Berner & Smith, 2004;Bland & Rubin, 1997;Ebdon, 2000).…”
mentioning
confidence: 99%